Reductions of Blood Lactate levels during and post sub-maximal eccentric exercises - Duffy, B. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
Can wearing a low value (10-12mmHg range) gradient compression garment (ankle to waist style) assist in reducing blood lactate levels immediately post sub-maximal eccentric exercise, and also reduce the time for blood lactate levels to return to pre eccentric exercise amounts? Two studies were conducted which involved testing rowers immediately post activity over four training periods. The first study, involving the Men`s Senior Rowing Eight (B) Team, under the coaching and supervision of Tim Conrad of Queensland Academy of Sport concluded that wearing such garments can reduce blood lactate levels by up to 42% during and immediately after such activity. The second study involved recovery post competition, and was conducted with the New South Wales Institute of Sport at Dunc Gray Velodrome during National Championships with the Men`s Under 19 3Km Pursuit Team. That study showed a reduction in clearing time of blood lactates from 33 minutes to 20 minutes to achieve a blood lactate level lower than 2mmol/l in the four competitors.